820 VARIABLE EXPRESSIVITY OF SCN5A MUTATION IN A FAMILY WITH CARDIAC DYSFUNCTION AND SUSPECTED BRUGADA SYNDROME. (15th December 2022) - Malizia, Biagio; Curcio, Antonio; Rodolfo, Iuliano; Colao, Emma; Pingitore, Elisabetta; Cardia, Giada; Romano, Letizia Rosa; Pasceri, Eugenia; Aquila, Iolanda; Indolfi, Ciro
Abstract: Background: Inherited arrhythmogenic diseases (IADs) represent a group of life-threatening genetic cardiomyopathies that predispose young individuals to sudden cardiac death (SCD), often in the absence of structural cardiac alterations. Some IADs share mutations in genes encoding for surface membrane ion channels, and the gene for the alpha subunit of the voltage-dependent channel Nav1.5 (SCN5A) is among the ones mostly involved. Brugada syndrome represents one of the possible spectrum deriving from SCN5A gene mutations, and it is characterized by "loss-of-function" genetic alterations. Interestingly, both loss-of and gain-of-function mutations have been associated with familial dilated cardiomyopathy (DCM). Materials and Methods: In the context of an Italian Ministry of Health-funded research project devoted to identify genetic isolates of IADs in the Calabria region, we found a family affected by different cardiovascular manifestations including cardiac dysfunction, ventricular tachyarrhythmias, atrioventricular block and suspected Brugada syndrome pattern in first-degree relatives in association with a newly identified SCN5A mutation. Results: The proband came to our attention with a diagnosis of DCM, echocardiographic assessment of reduced left ventricular ejection fraction (EF) to 38%, high occurrence of premature ventricular complexes (PVCs) and first-degree atrioventricular block (PR = 240ms) at electrocardiogram. In spite of negative electrophysiologic study, he underwent implantable cardioverter defibrillator implantation (ICD), hypothesizing lamin A/C mutation; genetic analysis turned out negative for lamin A/C and CACNA1C, while a SCN5A gene mutation (c.4554 G<T p.Gln1518His) was detected. Proband's sons and his brother underwent clinical evaluations as well as genetic testing: the second son's ECG showed first-degree AV block (PR = 220ms), QTc interval 426ms, and coved type ST-segment elevation of 1.5mm, in the context of normal cardiac function; the remaining male (see Figure 1) was asymptomatic, while the daughter had a hypokinetic non-dilated cardiomyopathy. The proband's brother had first-degree AV block and very frequent monomorphic ventricular couplets. Conclusions: These phenotypic differences in first degree-relatives, can be explained by the concept of variable expressivity of genes, according to which individuals carrying the same mutation can have different clinical features. Therefore, the search for genetic mutations assumes a preponderant role for stratifying the risk of SCN5A-related diseases and to adopt appropriate diagnostic and therapeutic strategies.